DOES TRADITIONAL CONFLICT RESOLUTION LEAD TO JUSTICE? — THE MATO OPUT IN NORTHERN UGANDA (The Pretoria Student Law Review, 2021)
It has been nearly 22 years since the start of war in northern Uganda, waged by the Lord’s Resistance Army (LRA) under the leadership of Joseph Kony. Kony started this war with the spiritual and traditional belief in the need to defend the Acholi people from the National Resistance Movement (NRM), led by Yoweri Museveni, who took over power in 1986 from the Acholi general Tito Okello. In this war, thousands of people have lost their lives and many others have been adducted. On 13 October 2005 the ICC issued warrants of arrest to the top five commanders. The commanders included Joseph Kony, Vincent Otti, Okot Odhiambo, Dominic Ongwen and Rasak Lukwiya, who is now deceased. Before these indictments were issued there was a lot of debate on whether these commanders should be tried by the ICC or the traditional justice system. This led to the passing of the Amnesty Act in 2000. ‘Amnesty’ in the Amnesty Act means pardon, forgiveness, exemption, or discharge from criminal prosecution or any other form of punishment by the state. Amnesty is declared in respect of any Ugandan who at any time since 26 January 1986 engaged in, or is engaging, in war or armed rebellion against the government of the Republic of Uganda. However, the people of northern Uganda have resorted to the traditional way of conflict resolution through the mato oput ritual, and the local population prefer this system to the one that the ICC will apply to ensure that justice is achieved. It is important to note that this ritual is performed only among the Acholi people. The question may be posed: what happens to other tribes in the northern part of the country who have also suffered as a result of this conflict? Will they benefit from this traditional ritual practice in that they will be able to forgive the perpetrators and reconcile with them? Will they see this as a form of justice being achieved? Can this ritual be relied on to achieve justice as an alternative to ICC trials? This article will address some aspects of the mato oput ritual and discuss whether justice could be achieved through this traditional method of conflict resolution.
Keywords: northern Uganda; war; Lord’s Resistance Army; Joseph Kony; National Resistance Movement; NRM; Amnesty Act; Amnesty; armed rebellion; ICC; conflict